(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The aim of the research is to use this technique and to determine the effect of this method in reduce cost per unit of the company. The traditional method used in the company the research sample to determine the indirect costs, the definition of the concepts and characteristics of the method of cost-based activity and the cost method based on time-driven activity and justifications applied to companies. In order to achieve the research objectives, the main hypotheses were formulated. That was represented: (The applied of (TDABC) Time driven activity based costing method in reducing indirect costs, leads reduce cost per unit than the use of the traditional method of allocating indirect costs in the research sample company). The research reached a set of conclusions and recommendations and the one that was the most important conclusions, the traditional method of the company does not provide cost-effective information that leads reduce cost per unit in the traditional way, unlike the TDABC method, which provides cost-effective information that helps the management in decision-making that leads to reduce cost per unit. One of the most important recommendations reached in the research that the company should adoption of the modern methods, which is the time-driven activity (TDABC), which provides information to help management in decision-making and the ease and speed in the application of the need to educate industrial companies in TDABC method to solve the problem of allocation of indirect costs in better form and distributed better and more fairly in the supporting departments, in addition to overcoming the disadvantages of the traditional method and the method of ABC and therefore depending to the time equations.